Ireland : 2017 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights Ireland' continued position among the euro area's top growth performers. Real GDP expanded by 5.2 percent in 2016, supported by a healthy expansion of private consumption and buoyant investment, including construction. Strong broad-based job creation brought unemployment down to 6.4 percent in May, its lowest level in a decade, while inflation remained low as the recent pickup in energy prices and upward pressure from services were partly offset by the impact of weakness in the British pound. The outlook remains positive, but with substantial, mainly externally driven, downside risks. Real GDP is projected to grow at 3.9 percent in 2017, propelled by strong domestic demand.